2021
DOI: 10.3390/microorganisms9112277
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Technologies to Study Phenotypic Heterogeneity and Bacterial Persisters

Abstract: Antibiotic persistence is a phenomenon in which rare cells of a clonal bacterial population can survive antibiotic doses that kill their kin, even though the entire population is genetically susceptible. With antibiotic treatment failure on the rise, there is growing interest in understanding the molecular mechanisms underlying bacterial phenotypic heterogeneity and antibiotic persistence. However, elucidating these rare cell states can be technically challenging. The advent of single-cell techniques has enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 157 publications
(205 reference statements)
0
10
0
Order By: Relevance
“…Previously, it has been used for antibiotic resistance studies [ 7 , 24 , 68 , 94 ]. Specifically, single-bacteria RNA-seq exhibits great potential in persister phenotypic exploration [ 95 ], since it allows for investigation under different environments and provides huge data to better understand the developmental trajectory of the persistent bacteria. A new technology named BacDrop, which was based on the microdroplet technique for bacterial single-cell RNA-seq, enables multiplexing and massively parallel sequencing [ 96 ].…”
Section: Recent Progress Of Technologies On Persister Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been used for antibiotic resistance studies [ 7 , 24 , 68 , 94 ]. Specifically, single-bacteria RNA-seq exhibits great potential in persister phenotypic exploration [ 95 ], since it allows for investigation under different environments and provides huge data to better understand the developmental trajectory of the persistent bacteria. A new technology named BacDrop, which was based on the microdroplet technique for bacterial single-cell RNA-seq, enables multiplexing and massively parallel sequencing [ 96 ].…”
Section: Recent Progress Of Technologies On Persister Studiesmentioning
confidence: 99%
“…These results demonstrated that persister cells showed distinct metabolic activity in the presence of the antibiotic. Compared to mass spectrometry, which is often used in proteome and metabolome analysis [ 98 ], Raman spectroscopy does not destroy samples, allowing for further downstream analyses [ 95 ]. Similarly, since most microdevices used are of a closed system nature, making the recovery and subsequent investigation of persister cells difficult, a directly accessible femtoliter droplet array was developed for persister collection and identification at the single-cell level [ 94 , 99 ].…”
Section: Recent Progress Of Technologies On Persister Studiesmentioning
confidence: 99%
“…The resulting cDNA is subjected to PCR amplification using primers (GAT27), and then prepared for sequencing library construction using transposase-assisted tagmentation [15] . In data analysis, the UMIs help elucidate the effects of PCR bias versus actual transcript abundance variations [43] , [45] .…”
Section: Multiple Annealing and Dc-tailing Based Quantitative Scrna-s...mentioning
confidence: 99%
“…In eukaryotic cell biology, measuring single-cell behaviors and cell-to-cell heterogeneity in a complex environment is key to understanding cellular interactions in different physiological conditions. For microorganisms, the heterogeneity in genotypic and phenotypic traits has a direct impact on human health and the functioning of environmental microbiomes. Consequently, the rapidly developing single-cell technologies have revolutionized microbiology. Among omics-based analyses, single-cell metabolomics provides the most immediate and dynamic picture of the functionality of a cell, but it is arguably the most difficult to measure. , Due to the small amount of metabolites present in single cells and the inability for amplification, detection sensitivity challenges are posed on metabolomics technology, especially when analyzing the comparably small bacterial and archaeal cells. Additionally, as the function of a cell in a given set of physiochemical conditions is a variable and dynamic property that cannot be reliably predicted from either metabolic reconstructions or genomics data alone, genotyping integrated with metabolic analysis provides a better way to understand how microorganisms interact with their biotic and abiotic environment.…”
Section: Introductionmentioning
confidence: 99%
“… 1 7 For microorganisms, the heterogeneity in genotypic and phenotypic traits has a direct impact on human health and the functioning of environmental microbiomes. 8 11 Consequently, the rapidly developing single-cell technologies have revolutionized microbiology. 12 16 Among omics-based analyses, single-cell metabolomics provides the most immediate and dynamic picture of the functionality of a cell, but it is arguably the most difficult to measure.…”
Section: Introductionmentioning
confidence: 99%